The Presumptive Effectiveness of Silver Nanoparticles in Treatment of Postpartum Endometritis in Dairy Cows - El-Amrawi, Gamal; Gad El-Karim, Dina R.S. (Journal of Advanced Veterinary Research, 2022)
Clinical postpartum endometritis due to bacterial invasion is one of the most common diseases affecting dairy cows in postpartum period; antibiotics are widely utilized as a treatment to overcome this affection. Recently, bacterial resistance to antibiotics due to uncontrolled usage became one of the most serious problems facing the medical community, so, the aim of study was to detect the effectiveness of nano-silver particles as a treatment for postpartum endometritis in dairy Holstein cows. At 35-40 days postpartum, twenty one Holstein cows were diagnosed to be affected with postpartum endometritis, depending on clinical and ultrasonography examination.Â The treatment protocol included intrauterine infusion with 50 ml of silver nanoparticles solution (50 ppm/ml) for five consecutive days, and single dose of PGF-2Î± analogue as a treatment for animals with a corpus lutetum on their ovaries. At 7th day post-treatment, serum level tumor necrosis factor-alpha (TNF-Î±), interleukin-6 (IL-6), C-reactive protein (CRP) and serum amyloid-A (SAA) and was significantly decreased (P<0.01). Also, the level of ceruloplasmin and haptoglobin (Hp)in serum recorded a significant decrement(P<0.05) upon treatment with silver nanoparticles.In addition, uterine secretions were found with a significant decrease or disappeared completely, and endometrial thickness decrement was detected upon ultrasonography examination. At re-examination (49-54 days postpartum), 14 animals out of 21 animals (66.6%) were recovered successfully from endometritis. The pregnancy rate on 40th day post-service was 71.4 % (10 out of 14 animals were found pregnant after insemination on their observed estrus).As a conclusion, this study proved the efficacy of silver nanoparticles as a treatment for postpartum endometritis in dairy Holstein cows. So, it could substitute antibiotic treatment in such cases to avoid the antibiotic resistance problems.